Development of taqman-based real-time rt-pcr assay for quantitative detection of feline morbillivirus (feMV) and phylogenetic analysis of Malaysian feMV isolates - Makhtar, Siti Tasnim (2021)
Feline morbillivirus (FeMV) of genus Morbillivirus is a novel emerging virus of domestic cats, linked with the development of CKD. Several quantitative diagnostic assays have been developed for the detection of FeMV such as reverse transcriptase loop-mediated isothermal amplification (RT-LAMP) and quantitative reverse transcriptase-polymerase chain reaction (qRT-PCR); however, none of the published assays targets the N gene of FeMV. N gene is one of the most conserved genes in morbilliviruses which also plays an important role in RNA synthesis by RdRp complex. In view for a specific and sensitive assay targeting local isolates, the objectives of this study were to develop Taqman-based qRT-PCR assay for the quantitative measurement of FeMV based on the sequence of N gene of local isolates and to assess the sensitivity and specificity of the developed qPCR assay in detecting FeMV. Sequence analyses of FeMV-Malaysia isolates were performed to develop specific primers targeting N gene. Phylogenetic analysis shown that the local isolates were closely related to the isolates from China, Thailand and Japan. Subsequently, a set of primers was designed and used in qRT-PCR assay which demonstrated a high specificity with no amplification signal towards other morbilliviruses and other feline viruses. Lowest limit of detection for the developed assay was at 1.74 x 10-4 copies/ߤL. The CV values for inter- and intra-assay variation were low, ranging from 1.38% - 2.03%, and 0.34% - 0.53%, respectively. Besides, the developed qRT-PCR assay was tested using cats’ urine and kidney samples. The findings were then compared with the detections using conventional RT-PCR. The developed qRT-PCR assay detected FeMV in 35.2% of cats’ samples compared to 15.5% by conventional RT-PCR. In conclusion, the developed assay of qRT-PCR has a high specificity and sensitivity in detecting FeMV compared to conventional RT-PCR, thus can be utilized as diagnostic tools and to determine possible association with CKD occurrence in cats.